Proposed New Retinopathy of Prematurity Screening Criteria: Evidence for Including Older and Heavier Filipino Premature Babies - Kristine Corpus, MD; Jose Melvin Jimenez IV, MD; Rachelle Anzures, MD; Rena Ivy Bascuna, MD; Ricardo Ventura, MD; Macario Reandelar Jr., MD, MSPH (Philippine Journal of Ophthalmology)
Objective: (1) To determine if preterm babies with ROP are missed with the existing Philippine Pediatric Society-Philippine Academy of Ophthalmology 2005 screening criteria of ≤32 weeks gestational age (GA) and ≤1,500 grams birth weight (BW), (2) to determine the incidence (missed-out rate) of these babies with ROP (>32 weeks GA, >1,500 grams BW), (3) to describe their profile, and (4) to determine the appropriate upper limit for GA and BW that can provide safe and efficient screening for severe ROP.